1990
DOI: 10.1159/000115293
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic Projections from a Midbrain Somatosensory Area in a Reptile, <i>Caiman crocodilus</i>

Abstract: Ascending projections to the thalamus from a midbrain somatosensory area were investigated in a reptile, Caiman crocodilus. Connections were determined utilizing horseradish peroxidase (HRP) neurohisto-chemistry in which tetramethylbenzidine was the chromogen. Anterograde experiments, in which HRP injections were placed into the midbrain, revealed bilateral projections to the medialis complex of the dorsal thalamus. These observations were confirmed by HRP injections into the medialis complex which retrogradel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Data on thalamo-telencephalic connections in lizards and other reptiles suggest that dorsal tier nuclei tend to receive "lemniscal" afferents and project into cortical telencephalic domains (derivatives of medial and dorsal pallial areas; Hoogland, 1981;Kü nzle and Schnyder, 1983;Bruce and Butler, 1984a,b;Butler, 1995;Kenigfest et al, 1997;Desfilis et al, 1998). In contrast, the nuclei in the middle and ventral tiers receive strong mesencephalic ("collicular") inputs (tectal, intercollicular, or toral) and project to specific areas in the telencephalic dorsal ventricular ridge (DVR; Pritz, 1974a,b;Pritz and Northcutt, 1980;Balaban and Ulinski, 1981;Belekhova et al, 1983;Bruce and Butler, 1984a,b;Pritz and Stritzel, 1990;Butler, 1995;Guirado et al, 2000). The DVR is a nuclear pallial domain, which has been recently classified into components derived from the lateral pallium and a newly identified component of the vertebrate pallium, the molecularly distinct ventral pallium (equal to the avian neostriatum; Puelles et al, 1999Puelles et al, , 2000; see also Striedter, 1997;Smith-Ferná ndez et al, 1998).…”
Section: Regional Subdivisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on thalamo-telencephalic connections in lizards and other reptiles suggest that dorsal tier nuclei tend to receive "lemniscal" afferents and project into cortical telencephalic domains (derivatives of medial and dorsal pallial areas; Hoogland, 1981;Kü nzle and Schnyder, 1983;Bruce and Butler, 1984a,b;Butler, 1995;Kenigfest et al, 1997;Desfilis et al, 1998). In contrast, the nuclei in the middle and ventral tiers receive strong mesencephalic ("collicular") inputs (tectal, intercollicular, or toral) and project to specific areas in the telencephalic dorsal ventricular ridge (DVR; Pritz, 1974a,b;Pritz and Northcutt, 1980;Balaban and Ulinski, 1981;Belekhova et al, 1983;Bruce and Butler, 1984a,b;Pritz and Stritzel, 1990;Butler, 1995;Guirado et al, 2000). The DVR is a nuclear pallial domain, which has been recently classified into components derived from the lateral pallium and a newly identified component of the vertebrate pallium, the molecularly distinct ventral pallium (equal to the avian neostriatum; Puelles et al, 1999Puelles et al, , 2000; see also Striedter, 1997;Smith-Ferná ndez et al, 1998).…”
Section: Regional Subdivisionsmentioning
confidence: 99%
“…Moreover, most recent studies on the reptilian thalamus deal with the extrinsic connectivity of the dorsal thalamus and especially with the visual thalamus (Dacey and Ulinski, 1983;Pritz and Stritzel, 1992;Kenigfest et al, 1997;Martinez-Marcos et al, 1998), whereas other "thalamic" regions, such as the ventral thalamus, the epithalamus, or the pretectum, are not addressed in detail. Exceptions to this are the studies of Pritz and Stritzel (1990) and Díaz et al (1994) on the reptilian reticular nucleus in the ventral thalamus.…”
mentioning
confidence: 97%
“…The medialis complex. which conveys nonfacial somatosensory information [Pritz and Stritzel, 1990a), sends axons to end in a central part of the DVR [Pritz and Stritzel, 1994a). Second, in cases where the anterograde termination of ascending connections has been determined (rotundus, reunions pars centralis, medi alis complex), the axons that leave each of these three nuclei, enter the dorsal peduncle of the lateral forebrain bundle, course dorsally to pass through and probably syn apse on interposed neurons of the ventrolateral area before ending in their respective targets in the DVR | Pritz, 1974a| Pritz, , 1975Pritz and Stritzel.…”
Section: Tltalamotelencephalic Connections In Caimanmentioning
confidence: 99%
“…First, each receives a bilateral input from the midbrain in which an ipsilalera! connection predominates and the con tralateral component is achieved by way of the supraoptic decussation [Braford, 1972: Pritz, 1974b: Pritz and Stritzel. 1990a], Second, the topographic location of each of these thalamic nuclei rellccts, in part, the location of each nu cleus' respective midbrain afferent.…”
Section: Non-cortical Thalamic Afferentsmentioning
confidence: 99%
“…These connections resemble those of the Dla in lizards [Hoogland, 1982]. In a recent review of the dorsal thalamus of jawed vertebrates, Butler [1994] suggested a possible homology between the caudal part of DLP in birds and a midbrain somatosensory recipient nucleus in the dorsal thalamus of diapsid reptiles, called the medialis complex in Caiman crocodilus [Pritz and Stritzel, 1990] and nucleus medialis posterior in lizards [Bruce and Butler, 1984a]. However, in light of the presence of multisensory (including trigeminal) afferents to both DLP and Dla, it is tempting to conclude that the Dla in lacertid lizards may be homologous to DLP and possibly other dorsal thalamic nuclei in birds.…”
Section: Comparative Remarksmentioning
confidence: 87%